Haemaphysalis longicornis subolesin controls the infection and transmission of severe fever with thrombocytopenia syndrome virus - Chuanfei Yuan; Yu Sun; Jingjing Chen; Qiong Xu; Xiang Zhou; Zhen Zou; Qianfeng Xia (npj Vaccines)
Abstract Severe fever with thrombocytopenia syndrome (SFTS) caused by the SFTS virus (SFTSV) is an emerging tick-borne disease with a high mortality rate. Haemaphysalis longicornis is the primary reservoir and vector of SFTSV. Here, we found that targeting subolesin (SUB), an anti-tick vaccine candidate, affects the infection and transmission of SFTSV in H. longicornis. RNAi-mediated knockdown of SUB repressed SFTSV infection in the salivary glands but not in the gut of H. longicornis, which may be associated with the modulation of protein processing in endoplasmic reticulum revealed by transcriptomic analysis. Knockdown of SUB decreased the survival and engorgement rates of ticks and impaired the horizontal and co-feeding transmission of SFTSV. Furthermore, active immunization with recombinant SUB inhibited the co-feeding transmission of SFTSV, although it had no significant effect on the blood-feeding behavior of infected ticks. Collectively, these results provide a potential target for controlling SFTS and other tick-borne viral diseases.